Reactive Power Compensation In Distribution Systems Using SAPF (International Journal of Engineering and Computer Science, 2018)
Traditionally when one imagine about power quality, images of classical waveforms comprising 3rd, 5th, 7th etc. harmonics come into picture .On this basis IEEE in team with industries and utilities  and academia began to attack this problem in “power quality ” from the 80s. However in last few years the term power quality has grown in meaning form a simple power system harmonics. Since the growth of the industries is inevitable with more complex and sensitive equipments involving semiconductor etc. the power quality engulfed a whole new dimension of errors that appear in power system. These issues or anomalies are becoming more unavoidable and growing strongly and sensitive equipments will become even more sensitive due to the fierce market competition. Now, efficiency and cost are treated as peer parameters of equal importance. In such a situation Active Power Filters have emerged as the solution in which SAPF is employed for removal of load current harmonics and reactive power compensation .Active filters for power conditioning offer the following: